Esther: uma prostituta judia em O ciclo das águas - Calixto, Lunara Abadia Gonçalves (2017)
This dissertation aims to analyze the book O Ciclo das Águas, written in 1975, by Moacyr Scliar. This book was inspired by the trafficking of Jewish women brought to America, in the early 20th century, where they were forced to be sex slaves. Being such a controversial subject, Scliar discusses a topic little known both in the context of History and Literature, in which prostitution of Jewish women happened because of pimps who were also Jews. In fact, Scliar presents a work with a great presence of symbolic elements, especially water and the feminine gender. The title O Ciclo das Águas refers to an analogy between the life of the character Esther and the symbolism of water, which in its movements and cycles, calm and rough, limpid and dirty, also represents the life of that character. This way, Moacyr Scliar creates a complex character, Esther, the Jewish prostitute, marked by moments of “clear waters and dark waters”, representing the life of other Jewish women who also lived this circumstance. Moacyr Scliar also problematizes the representation of women in the religious environment, specifically in the Judeo-Christian tradition, which proposes suitable spaces and appropriate actions, in a rigid moral code. For this, there is a "desecration" of these considerations in the way that Esther acts, thus evidencing a critique of the patriarchal society, which imposes that women follow actions pre-established to their gender, at risk of being excluded and marginalized.